2014
DOI: 10.4103/0253-7613.132191
|View full text |Cite
|
Sign up to set email alerts
|

Overdose of mycophenolate mofetil managed in a secondary care hospital in South India

Abstract: Mycophenolate mofetil (MMF) is a commonly used immunosuppressive agent and is considered relatively safe with minimal side-effects in therapeutic doses. However, data regarding the effects of an overdose is sparse and therefore, concerns remain regarding its safety. Here, we report the case of a 24-year-old young woman who consumed high dose (10 g) of MMF with suicidal intent. We did not observe any complications related to MMF overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A few of them developed self-limiting and mild symptoms like headache, nausea, vomiting, dizziness, and abdominal pain with a favorable outcome and none had any severe complications [ 3 ]. No symptoms and complications were reported after acute ingestion of 10 g of MMF in a 24-year-old patient who was taking the drug regularly for lupus nephritis [ 8 ]. Similar was the case in a 17-year-old female with granulomatosis with polyangiitis, who ingested 20 g of MMF at once [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few of them developed self-limiting and mild symptoms like headache, nausea, vomiting, dizziness, and abdominal pain with a favorable outcome and none had any severe complications [ 3 ]. No symptoms and complications were reported after acute ingestion of 10 g of MMF in a 24-year-old patient who was taking the drug regularly for lupus nephritis [ 8 ]. Similar was the case in a 17-year-old female with granulomatosis with polyangiitis, who ingested 20 g of MMF at once [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supratherapeutic overdoses are not common. Ceschi et al 7 present a review of overdose cases found in the literature up until now, in addition to the one from Alex et al 8 In transplant recipients, the highest MMF dose presented so far is 25 g, and the highest measured plasma concentrations of MPA is 44.1 mg/L (5 h after ingestion of 10 g MMF). Even therapeutic doses may, however, in rare circumstances, lead to high MPA trough values.…”
Section: Introductionmentioning
confidence: 99%